Collagen-I influences the post-translational regulation, binding partners and role of Annexin A2 in breast cancer progression - Mahdi, Amira F.; Nolan, Joanne; O’Connor, Ruth Í.; Lowery, Aoife J.; Allardyce, Joanna M.; Kiely, Patrick A.; McGourty, Kieran (Frontiers in Oncology, 2023)
The extracellular matrix (ECM) has been heavily implicated in the development and progression of cancer. We have previously shown that Annexin A2 is integral in the migration and invasion of breast cancer cells and in the clinical progression of ER-negative breast cancer, processes which are highly influenced by the surrounding tumor microenvironment and ECM. Thus, we investigated how modulations of the ECM may affect the role of Annexin A2 in MDA-MB-231 breast cancer cells. We have shown that the presence of collagen-I, the main constituent of the ECM, increases the posttranslational phosphorylation of Annexin A2 and subsequently causes the translocation of Annexin A2 to the extracellular surface. In the presence of collagen-I, we identified fibronectin as a novel interactor of Annexin A2, using mass spectrometry analysis. We then demonstrated that reducing Annexin A2 expression decreases the degradation of fibronectin by cancer cells and this effect on fibronectin turnover is increased according to collagen-I abundance. Our results suggest that Annexin A2's role in promoting cancer progression is mediated by collagen-I and Annexin A2 maybe a therapeutic target in the bi-directional cross-talk between cancer cells and ECM remodeling that supports metastatic cancer progression.